'It's a Man's Job': Doing Gender and Male Gatekeeping in the Division of Household Labor. - Christopher, Emily (Journal of Family Issues, 2024)
Changes to domestic divisions of labor have been widely documented, but some tasks seem particularly resistant to change. Using the lens of 'doing gender', this article draws on interviews with 25 heterosexual working parent British couples who produced a 'household portrait' of their division of labor. It examines how they explain men's continuing responsibility for 'man-typed' domestic tasks and why this is so resistant to change. Although men's 'gatekeeping' of these tasks is consequential for the overall household division of labor, there is relatively little opposition from their women partners. This gatekeeping reproduces gendered meanings of 'man-typed' tasks and enables both men and women to 'do gender' while supporting their image of a 'sharing' couple.